Inhibiting CXCL12 Blocks Fibrocyte Migration and Differentiation and Attenuates Bronchiolitis Obliterans in a Murine Heterotopic Tracheal Transplant Model - Harris, David A. (2012)
OBJECTIVES: Fibrocytes are integral in the development of fibroproliferative disease post lung transplantation. Undifferentiated fibrocytes (CD45+Col1+CXCR4+) preferentially traffic via the CXCR4/CXCL12 axis and differentiate into smooth muscle actin producing (CD45+CXCR4+αSMA+) cells. We postulated that an antibody directed against CXCL12 would attenuate fibrocyte migration and fibro-obliteration of heterotopic tracheal transplant allografts. METHODS: A total alloantigenic mismatch murine heterotopic tracheal transplant model of obliterative bronchiolitis was used. Animals were treated with either goat-anti-human CXCL12 F(ab′)(2) or Goat IgG F(ab′)(2). Buffy coat, bone marrow, and trachea allografts were collected and analyzed by flow cytometry. Tracheal luminal obliteration was assessed via hematoxylin/eosin and Direct Red 80 collagen stain. RESULTS: Compared to controls, anti-CXCL12 treated animals showed a significant decrease in tracheal allograft fibrocyte populations at 7 and 21 days post-transplantation. Bone marrow and buffy coat aspirates showed the same trend at 7 days. In anti-CXCL12 treated mice, there was a 35% decrease in luminal obliteration at 21 days (65.00 [interquartile range = 38]% vs. 100 [10]% obliterated; p=0.010) and decreased luminal collagen deposition at 21 and 28 days post transplantation (p=0.042 and 0.012, respectively). CONCLUSIONS: Understanding the role of fibrocytes in airway fibrosis post lung transplantation may lead to a paradigm shift in treatment strategy. Anti-CXCL12 antibody afforded protection against infiltrating fibrocytes and reduced deterioration of tracheal allografts. Thus the CXCR4/CXCL12 axis is a novel target for the treatment of fibro-obliteration post lung transplantation and quantification of fibrocyte populations may provide clinicians with a biomarker of fibrosis allowing individualized drug therapy.